Complexation of uranium(vi) with glutarimidoxioxime: thermodynamic and computational studies1. Issue 31 (21st August 2015) - Endrizzi, Francesco; Melchior, Andrea; Tolazzi, Marilena; Rao, Linfeng
<x xml:space="preserve">Abstract</x> Glutarimidoxioxime forms a bidentate complex with UO22+via the oxime and imino groups. Hydrogen bonding between water and the carbonyl group helps to stabilize the complex. The complex is much weaker than that of glutarimidedioxime previously studied.